Is The Implementation Of Self-Assessment Effective In Improving The Iranian EFL Students’ Writing? - Rahmanpour, Farzaneh; Janfaza, Abusaied; Soori, Afshin (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
Writing skill is an important skill which is a requirement for the future success of a learner, and providing feedback by teachers on the students’ writing a challenging issue. Self-assessment is almost a new trend in writing instruction. This study tries to investigate the effectiveness of the implementation of self-assessment in a writing classroom. To this end, 46 Iranian university students in Islamic Azad university, Kerman, Iran served as the participants of this study. The students were studying in English field of study. They were in a range of 20 to 24 who had taken the writing course voluntarily. In terms of the result of the proficiency test, the students were assigned randomly into two groups (an experimental and a control group). The students in the experimental group used self-assessment method and the students in the control group used the teacher assessment (traditional method) in the classroom. The findings of the current study revealed that the implementation of the self-assessment was helpful in the writing classroom and improved the overall abilities of the Iranian students.